Lung metastasectomy in patients with renal cell cancer (RCC). A 17-year experience in Parma Hospital - Ferretti, S.; Fornia, S.; Ampollini, et al., L. (Acta Biomedica Atenei Parmensis, 2007)
Aim: We aim to report the results of the curative, non-palliative, treatment of resection of lung metastases that are secondary to renal cell carcinoma (RCC). Methods: Between 1988 and 2004, a radical metastasectomy with curative purposes was performed in 20 (11 males and 9 females) patients with renal clear cell carcinoma (RCC) who had already undergone nephrectomy and subsequently metastasectomy of lung metastases. The mean age was 66,9 years (range 48-81 years). Results: the intraoperative mortality of patients undergoing surgical resection of lung metastases from RCC was 0%; 17 out of 20 patients returned at follow up; 9 patients died; the mean survival-time after nephrectomy was 64±42 months (range 7-132 months) and the mean survival-time after metastasectomy was 31±29 months (range 4-99 months); 4 out of 9 pts had pulmonary recurrence after surgery. 8 patients are still alive; the mean follow up after nephrectomy was 134±115 months (range 30-372 months) and 72±44 months (range 25-150 months) after metastasectomy. 1 out of 8 pts had a pulmonary recurrence that was treated by surgery. Conclusions: the radical resection of lung metastases is a safe and effective treatment in selected RCC patients.